Snake-shaped robot design and path planning algorithm - Zhao Guang-hui; Cheng Wan-sheng (Discover Computing)
Abstract Serpentine robots have broad application prospects in civilian, military, and other fields. However, recent developments in serpentine robot design, recent developments in snake-like robot design, mostly based on traditional algorithms, face several challenges in path planning and mapping. This study focuses on the snaking gait characteristics and proposes an improved path planning algorithm integrated with the robot’s mechanical design. The algorithm’s effectiveness is validated through simulation analysis. A functional relationship between the Serpentine locomotion control parameters and the motion shape parameters is established, enabling Serpentine locomotion path planning on the map based on the improved algorithm. The rationality and effectiveness of the proposed algorithm are verified through both simulation analysis and experimental validation. Real-world experiments are conducted using the developed snake robot prototype, and the results are compared with simulation outcomes. The findings confirm the rationality and effectiveness of the winding gait generation and path planning for obstacle avoidance, as well as the consistency between simulation and physical experimental results.